Awareness and knowledge of oral manifestations in cardiovascular diseases among the general public - S Shreenidhi; Vishnu Priya Veeraraghavan; R Gayathri; Jayaraman Selvaraj; S Kavitha (Wolters Kluwer Medknow Publications, 2022)
Cardiovascular diseases (CVDs) are disorders affecting the heart and blood vessels. Periodontal problems, bleeding gums, dry mouth, and gingival hyperplasia are common oral manifestations seen in cardiovascular-related problems. To assess the extent of awareness and knowledge, the general public has toward the oral manifestation related to that of CVDs. A questionnaire was distributed among the general public in relation to that of the extent of awareness and knowledge of oral manifestations with regard to CVD. A total of 161 responses were collected from the survey. The collected data were compiled and analyzed by the SPSS software; the Pearson Chi-square test was done where P < 0.05 was considered statistically significant. The study showed that 65.22% of the population is aware of the types of CVD. About 59.63% of the population do not know that periodontal problems lead to cardiovascular problems. About 39.75% have vague knowledge about the maintenance of poor oral health causing cardiovascular problems. The study concluded that the general public is not much aware of the oral manifestations related to that of CVDs.